Addressing Oxidative Stress and Endothelial Dysfunction in Chronic Respiratory Diseases: The Role of Exercise and Multidisciplinary Rehabilitation - Pasquale Ambrosino; Maria Nolano; Claudio Candia; Guido Grassi; Mauro Maniscalco (Antioxidants)
Chronic respiratory diseases (CRDs) are highly prevalent conditions, causing over 4 million deaths every year and representing a major source of physical, psychological, and occupational disability [...]